2016
DOI: 10.1519/jsc.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Player Load, Acceleration, and Deceleration During Forty-Five Competitive Matches of Elite Soccer

Abstract: The use of time-motion analysis has advanced our understanding of position-specific work rate profiles and the physical requirements of soccer players. Still, many of the typical soccer activities can be neglected, as these systems only examine activities measured by distance and speed variables. This study used triaxial accelerometer and time-motion analysis to obtain new knowledge about elite soccer players' match load. Furthermore, we determined acceleration/deceleration profiles of elite soccer players and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
268
9
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(329 citation statements)
references
References 30 publications
15
268
9
9
Order By: Relevance
“…Whereas our study showed the total number of accelerations and decelerations above 1.5 m · s −2 (226 and 169, respectively) and 3.0 m · s −2 (61 and 58), other studies that considered matches in elite leagues (Bradley et al 2010;Varley & Aughey 2013;Russell et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016) used absolute thresholds of 0.5, 2.0, 2.5, 2.78, 3.0 and 4.0 m · s −2 . It is important to realize that even if there was agreement, comparison between acceleration variables measured with different tracking systems (and system versions) would be difficult (Buchheit et al 2014b).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Whereas our study showed the total number of accelerations and decelerations above 1.5 m · s −2 (226 and 169, respectively) and 3.0 m · s −2 (61 and 58), other studies that considered matches in elite leagues (Bradley et al 2010;Varley & Aughey 2013;Russell et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016) used absolute thresholds of 0.5, 2.0, 2.5, 2.78, 3.0 and 4.0 m · s −2 . It is important to realize that even if there was agreement, comparison between acceleration variables measured with different tracking systems (and system versions) would be difficult (Buchheit et al 2014b).…”
Section: Discussioncontrasting
confidence: 82%
“…The average total distance ran during the matches in our study (10,927 m) reflected that of top-level leagues in Europe and Australia (range 10,063-11,230 m) (Bradley et al 2010(Bradley et al , 2013Osgnach et al 2010;Manzi et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016). Also running (14.4-19.8 km · h −1 ) distance and high-speed running (>19.8 km · h −1 ) distance were within the range of the same top-level leagues (1614 m vs. 1612-1758 m and 738 m vs. 646-1061 m, respectively).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The majority of research investigating physical demands of soccer competition have analysed total distance, and high-speed distances, but not considered acceleration activities (Bradley et al, 2009;Dellal et al, 2011, Di Salvo et al, 2010. Accelerations are highly fatiguing in nature, and with muscular fatigue responsible for a large proportion of injuries within soccer, consideration of accelerations are vital when assessing training load (Dalen et al, 2016;Ingebrigtsen et al, 2015). Of the limited research including acceleration analysis, arbitrary thresholds were utilised to determine acceleration intensity (Dalen et al, 2016;Ingebrigtsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%